BATHYMETRY MAPPING STUDY AS A CONSIDERATION IN DETERMINING SHIPPING CHANNEL IN PRAMUKA ISLAND WATERS, SERIBU ISLANDS, DKI JAKARTA - Agus Anugroho D.S; Petrus Subardjo; Bintang Yosua Cristian M. (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTBathymetry is a method or technique in determining sea-depth or seabed profile from the result of sea-depth analysis. Bathymetry data is an important data used as shipping channel consideration, especially in Pramuka Island Waters, Seribu Islands, DKI Jakarta. Determining shipping channel in Pramuka Island Waters is really important as the reference for secure sea traffic. The purpose of this study is to know bathymetry condition used as consideration in determining shipping channel in Pramuka Island Waters, Seribu Islands, DKI Jakarta. This reasearch was conducted in August, 4th – 6th 2016 on waters and dock of Pramuka Island, Seribu Islands, DKI Jakarta. The materials used as objects of this study are tidals, bathymetry and seabed morphology in Pramuka Island, Seribu Islands, DKI Jakarta. This research used case study method, i.e., research methods conducted intensively and detailed on a case, can be environment, certain situation to reveal or to understand something and the result can not be used in other areas. Case study in this research is knowing sea-depth. In this case, the result of this research which are bathymetry and shipping channel, cannot applied in other areas. Data processing using software Surfer 9.0, Arc Gis 10.3 and Microsoft Excel. The result of this research indicate that sea-depth in research location have depth between -0,7 until -38,6 m. Seabed morphology in Pramuka Island Waters was included in sloping category, with the slope value of 2,57% untill 10,12%. Tidal type is diurnal type with Formzahl value 3,34. Consideration of shipping channel due to vessel traffic is channel from North Jakarta direction and from other islands direction heading Pramuka Island. Key words: bathymetry, shipping channel, pramuka island waters